Effects of Origanum vulgare and Scutellaria baicalensis on the Physiological Activity and Biochemical Parameters of the Blood in Rats on a High-Fat Diet - Maryna Lieshchova; Viktor Brygadyrenko (Scientia Pharmaceutica, 2022)
The pharmacological effects of medicinal plants play a primary role in the mild correction of body weight in humans and animals, reducing the accumulation of fat in their bodies during a state of obesity. Origanum vulgare L. and Scutellaria baicalensis Georgi are widely used as food additives and medicinal plants, but their comprehensive physiological evaluation in model animals in a state of obesity has not been carried out. In a 30-day laboratory experiment on male rats which had developed obesity through a hypercaloric diet, the effects of adding the dry crushed grass O. vulgare or dry crushed roots of S. baicalensis to their feed was evaluated. During the experiment, the rats fed with O. vulgare increased in body weight to only 105.5% of their initial weight, while the body weight of the control group increased to 111.5%, and that of animals fed on S. baicalensis increased to 124.0% of their initial body weight. The average daily increase in the rats’ body weight when O. vulgare was added to their diet decreased to 205 mg/day, and when S. baicalensis was added, on the contrary, it increased to 1417 mg/day, compared to 700 mg/day among the control group. Under the influence of O. vulgare, the lipid metabolism of the rats normalized: the atherogenic index decreased to 33.7%, compared with the values of the control group, due to an increase in the concentration of high-density lipoproteins from cholesterol. The concentration of triglycerides decreased, and the concentration of glucose decreased. The roots of S. baicalensis being added into the diet of rats increased the activity of alkaline phosphatase and decreased the concentration of urea. The atherogenic index also decreased (by up to 35.5% in the control group) and the concentration of high-density lipoprotein cholesterol increased, while the concentrations of triglycerides and glucose decreased. The physical activity of the rats showed a slight tendency to decrease when both O. vulgare and S. baicalensis were added to their diet. Both plant species contributed to a decrease in the emotional status of animals, which was most pronounced when the O. vulgare grass was added to the feed. The results of the study demonstrate the potential of the use of O. vulgare and S. baicalensis as herbal supplementations for the correction of hyperlipidemia and type-2 diabetes mellitus in overweight patients.